Il fascino discreto delle mappe in letteratura: da Shakespeare a Ortelius - Pasqualin, Massimo (GEOmedia, 2017)
The term mapp'ry is analyzed through famous works of the English Renaissance. The author's intention is to explain the meaning of the ancient word, that disappeared from contemporary texts but useful to clarify the intrinsic value of cartography even today. The word becomes a metaphor for a mental strategy or a real object in the hands of political power. The literature of the past has helped to spread the knowledge of cartography using texts and plays written by great authors. The writers bring attention to the importance of maps during the golden age of geographical and scientific discoveries.